Identification of factors that influence technical efficiency of food crop production in West Africa - Amaza, P.; Bila, Y.; Iheanacho, A. (2006)
The objective of this study was to examine the determinants of food crop production and technical efficiency in the guinea savannas of Borno State, Nigeria. A stochastic frontier production function, using the maximum likelihood estimation (MLE) technique was applied in the analysis of data collected from 1086 sample farmers in 2004. The MLE results reveal that farm size; fertilizer and hired labour are the major factors that are associated with changes in the output of food crops. The effect of land area on output is positive and the coefficient found to be significant (p = 0.01). Fertilizer and hired labour have positive effects on output and their coefficients are significant (p = 0.01). Mean farmers’ technical efficiency index was found to be 0.68. Farmer-specific efficiency factors, which comprise age, education, credit, extension and crop diversification, were found to be the significant factors that account for the observed variation in efficiency among the farmers. The implication of the study is that technical efficiency in food crop production could be increased by 32 percent through better use of available resources, given the current state of technology.